AB1071 Primary bone non hodking's lymphoma: Presentation of 5 cases. (23rd January 2014) - Valls Roc, M.; Codina, O.; Roncero, J.M.; Muntane, M.J.; Sala, M.
Abstract : Background: Primary bone lymphoma (PBL) has been described as a malignant lymphoid bone infiltration, with or without cortical invasion and/or soft tissue extension, without visceral involvement nor distantlymph nodes. PBL constitutes 2% of all bone tumors and 5% of extranodal lymphomas. Sites commonly affected are the long bones and only 1-2% has primary vertebral locations. The common symptoms are inflammatory pain, palpable mass, pathologic fractures or spinal cord compression syndrome. In 50% of cases was B symptoms (fever, weight loss and night sweats) before and the majority are monostotic (80%). Histopathologically, the majority of cases has been diffuse large B-cell non-Hodgkin lymphoma but has been cases of follicular B-cell lymphoma. The usual treatment is chemotherapy with rituximab-CHOP regimen followed by radiotherapy if there is residual diseaseor spinal cord compression. Patients have 5 and 10 years overall survival of 60% and 45% respectively. Objectives: report 5 cases of PBL in a county hospital. Methods: 5 patients with PBL were collected; they were 2.5% of all lymphomas diagnosed in our hospital during 1995-2011. We analyzed the clinical features, laboratory and radiologic findings, treatment and follow-up of these patients. Results: 5 patients were diagnosed(3 men and 2 women), median age was 54 years (35-73). Four had inflammatory pain and one palpable mass. No patient had B symptoms. Analysis only showed alterations in acute phase reactants in two patients and the study of tumor markers, LDH levels and serum protein were normal in all patients. Plain radiographs showed only changes (vertebral fractures) in patient 3. Malignant lesion was suspected by MRI study (heterogeneous hypointense lesion on T1 and hyperintense on T2) and in patient 5 by radionucleotide 99m Tc bone scanning. CT scan not showed visceral involvement or lymphadenopathy in any patient. Only in one case (patient 3) bone biopsy showed bone marrow infiltration. The injury was monostotic in two cases and polyostotic in three. The histological diagnosis was confirmed by bone biopsy (WHO classification). Four were diffuse large B-cell lymphoma and one follicular B. Stage was assigned according to Ann-Arbor staging system, IE in two patients, IIE in two and IVE in one. Treatment consisted of radiation therapy to the patient 4 (follicular lymphoma) and chemotherapy with rituximab-CHOP regimen in three cases. Patient 5 was treated with chemotherapy according to CHOP regimen and required a second course of chemotherapy and autologous peripheral blood transplantation (ASCT) for cutaneous recurrence. Patients 4 and 5 obtained complete remission after treatment, while patient 4 died four years later from a hepatocellular carcinoma. To remark, in three patients extension study found presence of thyroid disease (two goiters and one nodule without malignancy). Conclusions: ThePBL is a rare bone tumor and especially if there is primary vertebral involvement. Symptoms and radiological findings are variable and nonspecific. Primary bone lesion biopsy is required for diagnosis. Disclosure of Interest: None Declared